2022
DOI: 10.1007/s12665-022-10619-y
|View full text |Cite
|
Sign up to set email alerts
|

Environmental fragility as an indicator of the risk of contamination by human action in watersheds used for public supply in western Paraná, Brazil

Abstract: Applying environmental fragility in studies evaluating watershed can guide policy decisions on monitoring and management regarding soil use planning, improving water quality for public supply. The objective of this study is to characterize the environmental fragility as well as to relate it to water quality factors of catchment rivers for public supply in western Paraná, Brazil, in order to evaluate the in uence of anthropic actions on catchment sources. Water quality data such as temperature (Temp; C), electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 62 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…Studies conducted in the same watershed consolidated the effects of urbanization and agriculture on limnological variables (Medeiros et al, 2020). When assessing environmental fragility (calculation performed using slope, soil type, and landscape) Peres et al (2022) found that the watershed of the Cascavel River presents a high environmental fragility, being one of the most impacted in the western region of the state of Paraná, Brazil.…”
Section: Discussionmentioning
confidence: 98%
“…Studies conducted in the same watershed consolidated the effects of urbanization and agriculture on limnological variables (Medeiros et al, 2020). When assessing environmental fragility (calculation performed using slope, soil type, and landscape) Peres et al (2022) found that the watershed of the Cascavel River presents a high environmental fragility, being one of the most impacted in the western region of the state of Paraná, Brazil.…”
Section: Discussionmentioning
confidence: 98%
“…Increasingly, lotic environments are degraded due to urbanization and intense anthropic activities (Li et al 2022). In this context the water for public supply is deteriorated, besides all aquatic biota that suffer the consequences of inadequate management of these environments (Peres et al 2022). In this sense the taxonomic composition of the Class Chlorophyceae is an important tool to assist in environmental diagnosis, since the species are often associated with environments with organic pollution and potential eutrophication (Wijeyaratne & Nanayakkara 2020).…”
Section: Introductionmentioning
confidence: 99%